Analisis Kapasitas Ruang Parkir Sepeda Motor Pada Pelabuhan Ipi Ende - Gare, Mansuetus; Kota, Ireneus; Luis, Andreas (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2023)
Parking is a special place for vehicles to stop for a while. Problems with the area of parking lots and the number of vehicles often occur in developing cities in Indonesia today. This has also happened in the city of Ende, especially in the Ipi harbor motorbike parking area which was affected by the increase in the number of residents and the number of vehicle activities. In order to find a safe parking space, it is necessary to do some research. This study aims to determine the value of parking characteristics and capacity (service capability) of motorbike parking spaces in Ipi Ende port. The method used in this study was direct observation (observation) which was carried out for 3 days. The data taken is in the form of parking volume, parking accumulation and parking duration. The data was then processed using